Towards efforts to enhance tax revenue mobilisation in Africa: Exploring the interaction between industrialisation and digital infrastructure - Pamela Efua Ofori; Isaac Kwesi Ofori; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
Motivated by the momentous rise in the new economy, the implementation of the African Continental Free Trade Area agreement, and the expected rebound of foreign direct investment to Africa from 2022, this study examines the joint effects of industrialisation and digital infrastructure on resource mobilisation in Africa. To this end, we mine data for 42 African countries for the analysis. The results, which are based on the system GMM estimator show that although unconditionally both industrialisation and digital infrastructure enhance (i) goods and services tax (GST), and (ii) profits, corporate and income tax (PCIT) mobilisation efforts in Africa, the effects of the former is rather remarkable in the presence of the latter. Particularly, we find that although all our digital infrastructure dynamics amplify the effect of industrialisation on GST, only ICT usage and ICT skills matter for PCIT. Second, the study unveils ICT thresholds for complementary policies. Accordingly, industrialisation and ICTs are necessary and sufficient conditions for tax revenue mobilisation only below some ICT thresholds. Above these ICT thresholds, complementary policies are needed to maintain the overall positive incidence on tax revenue mobilisation. Policy recommendations are provided in the end.
Keywords: C33; F6; H2; H71; O33; O55; 330; AfCFTA; Africa; ICT access; ICT diffusion; Industrialisation; Tax; Revenue